Wide_Area Robust SMES Controller Design using Synchronized PMUs for Stabilization of Interconnected Power System with Wind Farms - Issarachai Ngamroo; Cuk Supriyadi Ali Nanda; Sanchai Dechanupaprittha; Masayuki Watanabe; Yasunori Mitani (My University, 2010)
Abstract The high penetration of wind power into interconnected power system may cause the severe problem of inter‐area oscillations. To stabilize power oscillations, superconducting magnetic energy storage (SMES), which is capable of controlling active and reactive powers simultaneously, can be applied. To achieve the practical SMES controller design, this paper focuses on a robust SMES controller design based on wide‐area synchronized phasor measurement units (PMUs) in an interconnected power system with wind farms. The structure of active and reactive power controllers of SMES is the first‐order lead/lag compensator. Assuming that multiple PMUs are located in an interconnected power system, the steady‐state phasor data are obtained by applying the small load perturbation. Using the phasor data, the simplified oscillation model (SOM) included with SMES power controllers can be identified and applied to estimate the dominant inter‐area oscillation modes. In the design, unstructured system uncertainties such as various operating conditions, system parameters variation, random wind patterns, etc., are represented by the inverse additive perturbation. To enhance the system robust stability margin, the optimization of SMES control parameters is solved by genetic algorithm in the SOM. Simulation studies in the West Japan six‐machine power system confirm that the robustness of the proposed SMES is much superior to that of the conventional SMES against various operating conditions. Copyright © 2010 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.
Keywords: Tie line; Robustness; Units of measurement; Phasor measurement unit; Frequency Control in Power Systems